2016
DOI: 10.1080/15438627.2016.1222281
|View full text |Cite
|
Sign up to set email alerts
|

Who runs the fastest? Anthropometric and physiological correlates of 20 m sprint performance in male soccer players

Abstract: The aim of the present study was to examine the relationship of 20 m sprint performance with anthropometrical and physiological parameters in male soccer players. A hundred and 81 soccer players from the region of Athens (age 23.4 ± 5.0 yrs, body mass 73.4 ± 7.7 kg, height 180.0 ± 5.9 cm, body fat (BF) 14.4 ± 3.6%), classified into quartiles according to 20 m sprint time (group A, 2.84-3.03 s; group B, 3.04-3.09 s; group C, 3.10-3.18 s; group D, 3.19-3.61 s), participated. Soccer players in group A were younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
2
18
0
2
Order By: Relevance
“…Some investigations explored the association between body composition (namely body fat or adiposity) and physical performance in soccer [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Brocherie and collaborators [ 41 ] found that the sum of six skinfolds associated with adipose mass index was largely correlated with speed decrements in a repeated-sprint ability (RSA) test in a group of 16 players from senior male Qatar national team.…”
Section: Body Composition In Soccermentioning
confidence: 99%
“…Some investigations explored the association between body composition (namely body fat or adiposity) and physical performance in soccer [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Brocherie and collaborators [ 41 ] found that the sum of six skinfolds associated with adipose mass index was largely correlated with speed decrements in a repeated-sprint ability (RSA) test in a group of 16 players from senior male Qatar national team.…”
Section: Body Composition In Soccermentioning
confidence: 99%
“…Soccer is considered a high-intensity and intermittent sport, with players involved in long periods of competition, interspersed with periods of recovery or less intense activity [9,10]. One of the most important variables for measuring performance in soccer is physical condition besides technical and tactical parameters [11]. To evaluate the physical conditioning, the Running Anaerobic Sprint Test (RAST) is commonly used [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Body fat percentage (BF%) is probably the most evaluated body composition component in sports [ 1 ]. In soccer, BF% estimation is part of the habitual assessment [ 2 ], because it is related to exercise performance [ 3 , 4 ], may be useful in seasonal monitoring [ 5 , 6 ], and may help compare players in different playing positions [ 3 , 7 9 ] and experience [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%